Development of test stand for experimental investigation of chemical and physical phenomena in Liquid Rocket Engine - Santos,Emerson Andrade (2011)
Abstract The main objective of this work was to present the specification of an experimental firing test stand for liquid rocket engines (LRE) and develop a program for control and acquisition of data. It provides conditions to test rocket engines with thrust from 50 to 100 kgf. A methodology for laboratory work implementation using information technology, which will allow the automatic and remote functioning of the test stand, permits users to input the necessary data to conduct tests safely, achieve accurate measurements and obtain reliable results. The control of propellant mass flow rates by pressure regulators and other system valves, as well as the test stand data acquisition, are carried out automatically through LabVIEW commercial software. The test stand program is a readable, scalable and maintainable code. The test stand design and its development represent the state of art of experimental apparatus in LRE testing.